Functional Heterogeneity of the Young and Old Duplicate Genes in Tung Tree (Vernicia fordii) - Jiang, Lan; Fan, Tingting; Li, Xiaoxu; Xu, Jun (Frontiers in Plant Science, 2022)
Genes are subject to birth and death during the long evolutionary period. Here, young and old duplicate genes were identified in Vernicia fordii. We performed integrative analyses, including expression pattern, gene complexity, evolution, and functional divergence between young and old duplicate genes. Compared with young genes, old genes have higher values of Ka and Ks, lower Ka/Ks values, and lower average intrinsic structural disorder (ISD) values. Gene ontology and RNA-seq suggested that most young and old duplicate genes contained asymmetric functions. Only old duplicate genes are likely to participate in response to Fusarium wilt infection and exhibit divergent expression patterns. Our data suggest that young genes differ from older genes not only by evolutionary properties but also by their function and structure. These results highlighted the characteristics and diversification of the young and old genes in V. fordii and provided a systematic analysis of these genes in the V. fordii genome.